Is Medicines Parallel Trade "Regulatory Arbitrage'"? - Joan Costa-i-Font (Center for Economic Studies and ifo Institute (CESifo), 2015)
In the European Union, medicines are regulated products subject to both single market (e.g., regional exhaustion of property rights) and country specific health care regulations (e.g., medicines pricing). This gives rise to parallel trade (PT), a phenomenon that takes place when a patented product is diverted from the official distribution chain of one country to another parallel one where it competes with the official distribution chain. We argue that parallel trade of heavily regulated medicines conflicts with traditional sources of arbitrage (e.g., price and income differences) and instead is a form of regulatory arbitrage' that does not produce equivalent welfare effects. We draw upon a unique dataset that contains records of both origin and destination flows of parallel imported medicines to the Netherlands, for one therapeutic group (statins) that accounted for 5% of the market at the time of study and faced no generic competition. Our findings suggest that after controlling for country of origin (source) effects, parallel trade flows are primarily determined by medicines distribution chain regulation, and not by price differences in line with the hypothesis of regulatory arbitrage'.
Keywords: I18; L51; 330; parallel trade; regulatory arbitrage; pharmaceuticals; supply chain